Government Policy Instruments In Combating Illegal Fishing In Maluku Province - Sherly Adam; Hisnindarsyah Hisnindarsyah (JURNAL BELO, 2022)
The practice of illegal fishing in Indonesian waters is increasingly, especially in the waters of Maluku. This can be seen in the rising prevalence of illegal fishing by foreign vessels in several Maluku waters, which have a wealth of fishery resources with great potential. Indonesia already has a Law that regulates the problem of illegal fishing, namely Law No. 31 of 2004 concerning Fisheries. However, because of the increasingly complex problem of illegal fishing in Maluku waters, the law's implementation has been ineffective. As a result, the Maluku government has a role to play in combating illegal fishing in Maluku Province. The method used in this study is normative juridical research. The results showed that policy instruments that can be used by the government in combating the problem of Illegal Fishing in Maluku waters through minimal or preventive actions through the development and strengthening of the supervision system (law enforcement) at sea and maximum or repressive actions through government decisive actions by sinking and burning vessels resulting from criminal acts in accordance with the applicable law. The role of the Maluku Provincial Government and law enforcement officials is needed in combating an illegal, unreported, and unregulated (IUU) Fishing perpetrators based on applicable laws and regulations so that it can provide a deterrent effect for perpetrators in addition to increasing regional and international cooperation in combating an illegal, unreported, and unregulated (IUU) Fishing.